Allelopathic invasive plants as phytoinhibitor bioresource material in weed control: A review - Jiang Lim, Chaw; Kiang Lim, Chan; Cheng Lian Ee, Gwendoline (Agriculture and Natural Resources, 2019)
The current status was addressed of chemical pesticides use in raising crop productivity and the judicious utility of natural products from invasive plants which can promote inhibitory activity for noxious weed management. Some allelopathic invasive plants have natural phytoinhibitors which can be used in agricultural crop protection to compensate the drawbacks from chemical pesticide use. The potential allelochemicals attributed to some invasive plants and their modes of action are discussed. In addition, luxuriant invasive plants could provide a rich biomaterial source of inexpensive alternatives for weed control in forging the eco-sustainable development of agriculture.